Contemporary Arabic ArchitectureAnd It’s Local Specialism - Nedihal K, Naqa; Abdul Amir K, Nawal (Anbar Journal of Engineering Sciences, 2010)
To create an architecture with a local identity, expresses its environment convenient with contemporary time, we need to examine the architectural traditions of the region and get interest from the results which produced by old architects to be suited with natural and social circumstances. Confusing ideas and non related modern architectural products in addition to the incorrect following to the modern movements, led to lose the local identity and to harden distinguish among different environments (general problem) then there’s no closeness with those products and feeling estrangement from them because they forced to our Arabic environment, by copying known architectural compositions here & there in regions with civil and social values different entirely from the west. Generally some of new architects (practically) , and specifically our student (academically) concern with western Architecture more than Islamic Arabic architecture history (specific problem) then the research problem is :there is non _clarity of means which might be a common base and guide for our new Architects & students to create a local architecture harmonize with society & environment , therefore the main objective of the research is: to come out with clear image about these means & fix them in our student minds in architectural schools (for both of academically & practically fields ) Accordingly we have to return to our traditions and investigate their properties and use them in such a way suitable with needs of time and progressive technology. That doesn’t mean we have to metaphor formal and external language but we have to analyses the traditions and derive the distinguished sides and using them in modern way to create new modern architecture with local identity.